Personalized patient ventilation at large scale: Mass Ventilation System (MVS) - Melvin-Omone, Ogbolu (2022)
This paper describes a Mass Ventilation System (MVS) which serves as a medical ventilator system. It can be used to ventilate large number of COVID-19 patients in parallel (5 – 50+) with personalized respiratory parameters.  The system has been designed to be medically suitable for both non-invasive and invasive patient ventilation. It protects healthcare workers with its centralized air filtering solution, it increases the effectiveness of the healthcare workers with its networked communication and it can be operated in a temporary emergency hospital setup. In this paper, we describe the basic concept and building blocks of the system.